Students’ Engagement In Google Meet Sessions And Its’ Impact On Their Academic Performance: The Case Of Master’s One Students In The Department Of English At Mouloud Mammeri Univeristy - Benaissa, Amel; Yassine, Souryana (The Journal of Studies in Language, Culture, and Society, 2025)
The present research is a case study that looks at how first-year Master’s students’ behaviourally, cognitively, emotionally, and agentically engaged in their online Google Meet classrooms The target population is Master’s students in the Department of English, at Mouloud Mammeri University. The context of the study is mainly online e-learning classrooms in remote learning environments. To meet the goals the present study, an engagement survey, attendance data, and test scores, are used to collect data on students’ engagement. The primary tool used for data collection is a survey administered to 82 Masters’ students. It is designed to gather quantitative data about students’ engagement. Triangulation with observable behavioral data further supports the quantitative nature of the study. The four-dimentional model of students’ engagement, as proposed by Reeve & Tseng (2011), is used to design the research instruments of the present study. The results indicate that students generally have positive emotional engagement towards the use Google Meet as a learning and teaching platform. However, most students find it challenging to concentrate during online lessons and to retain what they have learned. Additionally, the data reveal that the students who regularly attended the online classrooms had better examination scores than the students who did not.